2007
DOI: 10.1021/ja071306+
|View full text |Cite
|
Sign up to set email alerts
|

Prototypical Phosphorus Analogues of Ethane:  General and Versatile Synthetic Approaches to Hexaalkylated P−P Diphosphonium Cations

Abstract: Versatile alkylation reactions give access to symmetric, homoleptic nonsymmetric, and heteroleptic symmetric hexaalkylated 1,2-diphosphonium derivatives as bottleable salts in high yields. A series of 1,2-diphosphonium salts has been isolated and characterized, representing prototypical phosphorus analogues of ethane. Additionally, the solid-state structures for four derivatives have been determined crystallographically. Nonsymmetrically substituted derivatives of 1,2-diphosphonium cations enable the direct ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
67
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 32 publications
6
67
1
1
Order By: Relevance
“…The strategy was initially used by Schmutzler to make 1, [8] later it was expanded to bis(triflates) by Alder to make 2, [9] and recently it has been applied to a range of acyclic diphosphines 4 a-d by Burford. [10] The latter author has also shown that the modified classical alkylating strategy, using tBuCl and GaCl 3 as reagents, gives the rather bulky 1,2-dication 4 d in good yield. [10] On the other hand, 3 was prepared by electrochemical oxidation of tris(diethylamino)phosphine PA C H T U N G T R E N N U N G (NEt 2 ) 3 .…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The strategy was initially used by Schmutzler to make 1, [8] later it was expanded to bis(triflates) by Alder to make 2, [9] and recently it has been applied to a range of acyclic diphosphines 4 a-d by Burford. [10] The latter author has also shown that the modified classical alkylating strategy, using tBuCl and GaCl 3 as reagents, gives the rather bulky 1,2-dication 4 d in good yield. [10] On the other hand, 3 was prepared by electrochemical oxidation of tris(diethylamino)phosphine PA C H T U N G T R E N N U N G (NEt 2 ) 3 .…”
mentioning
confidence: 98%
“…[7] A complete list of structurally characterised 1,2-diphosphoniums is shown in Scheme 1. [8][9][10][11] There are two general synthetic methods towards 1,2-diphosphoniums, namely oxidation of tertiary phosphines (top equation in Scheme 2) and alkylation of tetraalkyldiphos-Abstract: Syntheses and full characterisation data (including single crystal diffraction) of three 1,2-diphosphonium dicationic species with the naphthalene-1,8-diyl (Nap) backbone are reported. The oxidation of Nap[P-A C H T U N G T R E N N U N G (NMe 2 ) 2 ] 2 with P 2 I 4 to its 1,2-dication was achieved.…”
mentioning
confidence: 99%
“…Imposition of a cationic charge on a molecule containing a phosphine centre enables Lewis acid behavior that diversifies the chemistry of phosphorus. Complexes of RNP + (1) [1] , R 2 P + (2) [2] , RP 2+ (3) [2a, 2b, 3] , R 3 P-PR 3 2+ (4) [4] and P 3+ (5) [5] have been reported with a variety of ligands. [6] In addition, bipyridine complexes of P 3+ (6) [7] illustrate the potentially versatile coordination chemistry of phosphorus.…”
mentioning
confidence: 99%
“…tungsten complex of a cyclic phosphinophosphonium (Scheme 6b). 58,59 The phosphine centre in [(PMe 3 )PMe 2 ] 1+ can be alkylated to give [P 2 Me 6 ] 2+ , 60 which is analogous to methylation of a triphosphenium cation (Scheme 6c). 61 Single and double coordination of transition metals at lone pairs of neutral P(I) centres has also been reported (Scheme 6d-f, Fig.…”
Section: Coordination and Oxidation Of Lone Pair Bearing Acceptor-cenmentioning
confidence: 99%